A Rare Association of Atrial Septal Defect with Retinitis Pigmentosa in an Adult: Coincidence or Syndromic Link - Sumedh Krishna; Vignessh Raveekumaran (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Atrial Septal Defect (ASD) and Retinitis Pigmentosa (RP) are individually well-recognised clinical entities, but their co-occurrence in an adult patient without a defined syndromic diagnosis is exceptionally uncommon. A 52-year-old female with Type 2 Diabetes Mellitus (T2DM) who presented with acute gastroenteritis complicated by septic and hypovolemic shock. During evaluation, she was incidentally found to have an ostium secundum ASD measuring 1.07 cm with left-to-right shunt, dilated right-sided cardiac chambers, dilated main pulmonary artery and Pulmonary Arterial Systolic Pressure (PASP) of 43 mmHg. Ophthalmological assessment revealed bilateral advanced RP, with Visual Acuity (VA) limited to light perception in both eyes and fundus findings of peripheral bone-spicule pigmentation, attenuated retinal vessels and optic disc pallor. The family history was strongly suggestive of inherited retinal disease, with multiple siblings affected by progressive visual loss and a background of consanguinity. During admission, the patient developed a transient episode of left upper limb weakness, clinically consistent with Transient Ischaemic Attack (TIA); neuroimaging showed no acute infarct. Usher syndrome was excluded by audiometry (normal bilateral hearing) and that Bardet-Biedl syndrome and Refsum disease were excluded on separate clinical grounds. The present case is reported because the non syndromic co-existence of ASD and RP may represent a coincidental association or an unrecognised shared genetic/ developmental pathway. The case emphasises the need for multidisciplinary evaluation, genetic counselling and consideration of whole-exome sequencing in adults with congenital cardiac anomalies and familial retinal dystrophy.